Shifting preferences for choice‐making opportunities through histories of differential reinforcer quality. Issue 1 (9th October 2018) - Drifke, Melissa A.; Tiger, Jeffrey H.; Gifford, Margaret R.
Abstract : Children of both typical and atypical cognitive development tend to prefer contexts in which their behavior results in a choice of reinforcers rather than a single reinforcer, even when the reinforcer accessed is identical across conditions. The origin of this preference has been attributed speculatively to behavioral histories in which choice making tends to be associated with differentially beneficial outcomes. Few studies have evaluated this claim, and those that have, have yielded mixed results. We provided five preschool‐aged children experiences in which choice‐making and no‐choice contexts were differentially associated with higher preference and larger magnitude reinforcers, and we assessed changes in their preference for choice and no‐choice contexts in which outcomes were equated. These conditioning experiences resulted in consistent and replicable shifts in child preference, indicating that preference for choice is malleable through experience.